Perovskite Solar Cells with Front Surface Gradient. Issue 28 (9th June 2021) - Guo, Mingxuan; Bo, Jun; Chen, Xingtong; Wan, Peng; Chen, Mengyu; Li, Qinyi; Luo, Chengzhao; Chen, Yu; Chen, Song
Abstract: The recombination flux in a solar cell is determined by not only recombination centers, but also the spatial distribution of minority carriers. For halide perovskite solar cells (PSCs), although there has been a tremendous amount of work focusing on defect passivation, the issue of carrier distribution is not as well studied as for other types of solar cells. Here in this work, with the incorporation of perovskite quantum dots, the concept of the front surface gradient in PSCs using a solution process is successfully realized. Evidenced by multiple characterization techniques, the minority carriers are pushed away from the defect‐rich surface by the gradient of valence band maximum, which effectively reduces surface recombination without compromising photocurrent. As a result, the normal structured hybrid PSCs and MAPbI3 cells exhibit open‐circuit voltages exceeding 93% and 90% of their respective Shockley–Queisser limits, and the power conversion efficiencies reach 22.36% and 20.53%, respectively. Abstract : For a solar cell, the spatial distribution of minority carriers plays a key role in determining the recombination flux. By introducing a front surface gradient to push the minority carriers away from the defect‐rich surface, a high open‐circuit voltage (93% of the Shockley–Queisser limit) and power conversion efficiency (22.36%) are archieved for perovskite solar cells without defect passivation.